Direct measurement of magnetic monopole charge and transport dynamics - Hsu, C (2024)
Magnetic monopoles are magnetic excitations with quantized magnetic charge whose existence in pyrochlore spin ice materials has been studied widely. As a platform to study the hypothetical magnetic monopoles, classical spin ices have aroused fundamental interest. Despite the extensive studies, the transport theory of the magnetic monopole fluid remains elusive, especially indicated by the recent investigation with noise spectroscopy. This thesis endeavors to elucidate the dynamics of the monopole fluid by developing advanced SQUID-based spectrometer and provides several unique pieces of evidence towards the dynamical mechanism.